If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -3y = 108 Solving 12 + -3y = 108 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -3y = 108 + -12 Combine like terms: 12 + -12 = 0 0 + -3y = 108 + -12 -3y = 108 + -12 Combine like terms: 108 + -12 = 96 -3y = 96 Divide each side by '-3'. y = -32 Simplifying y = -32
| 12-3y=q | | 2y-16=-9 | | X=-1/5y-3 | | 1.9/6=x/1 | | 12-3=108 | | 1m+3-5=2 | | -2/3t+1/6=7/2t+5/6 | | y=-16x^2+234 | | 500-4P=-100+2P | | 6y+3x=6 | | 5m-5m=-8-m+3m | | X=-1/5y-e | | 756/0.09 | | (8x+10)+(11x+10)= | | 73142=n+81607 | | 2x-2/2 | | 3x^2+5x-7=x^2+8x+28 | | 4(2a-3)=2 | | 9x-3x+2=26 | | 248-8x=y | | m/6-23=-15 | | 8+2X/-3 | | 73142=n-81607 | | 1/4=s+1/12 | | x+x+4+x=4+2x+4 | | y=-2x^2+28x-2 | | 9(-7+m)=-36 | | 9x+-2x=-42 | | -2y+4=-4 | | 2(2x+3)=3x+11 | | 6x-9=19+4x | | b/9+1/7=20 |